2014
DOI: 10.1051/0004-6361/201118270
|View full text |Cite
|
Sign up to set email alerts
|

A library of near-infrared integral field spectra of young M–L dwarfs

Abstract: Context. At young ages, low surface gravity affects the atmospheric properties of ultracool dwarfs. The impact on medium-resolution near-infrared (NIR) spectra has only been slightly investigated at the M-L transition so far. Aims. We present a library of NIR (1.1-2.45 µm) medium-resolution (R ∼ 1500-2000) integral field spectra of 15 young M6−L0 dwarfs. We aim at deriving updated NIR spectral type, luminosity, and physical parameters (T eff , log g, M, L/L ) for each source. This work also aims at testing the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
204
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 143 publications
(230 citation statements)
references
References 190 publications
(409 reference statements)
24
204
1
Order By: Relevance
“…This indicates a photosphere with temperature around 2800 K (see e.g. Bonnefoy et al 2014, and references therein). Even if HS 0220+0603 followed the semi-empirical sequence of Knigge et al (2011) and had a donor mass of 0.25 M , the spectral type would still be cooler than expected.…”
Section: The M-type Companionmentioning
confidence: 91%
“…This indicates a photosphere with temperature around 2800 K (see e.g. Bonnefoy et al 2014, and references therein). Even if HS 0220+0603 followed the semi-empirical sequence of Knigge et al (2011) and had a donor mass of 0.25 M , the spectral type would still be cooler than expected.…”
Section: The M-type Companionmentioning
confidence: 91%
“…The third sample is made of spectra of members of 1−150 Myr old young moving groups and clusters (Lodieu et al 2008;Rice et al 2010;Bonnefoy et al 2014;Gagné et al 2014). The fourth sample is composed of spectra of young MLT companions (Patience et al 2010;Lafrenière et al 2010;Wahhaj et al 2011;Bonnefoy et al 2010Bonnefoy et al , 2014). …”
Section: Appendix A: Details On the Orbital Fitmentioning
confidence: 99%
“…The SED and spectral-fitting procedures are described in Bonnefoy et al (2013) and Bonnefoy et al (2014), respectively.…”
Section: Appendix A: Details On the Orbital Fitmentioning
confidence: 99%
“…Gorlova et al 2003;McGovern et al 2004;Kirkpatrick et al 2006 2007). We measured the equivalent widths (EW) of the gravity sensitive Na I doublet at 1.138µm and the K I doublets at 1.169, 1.177µm and 1.243, 1.253µm with associated errors as described in Bonnefoy et al (2014), with the psuedocontinuum wavelength regions reported therein. For a given spectral subtype, low surface gravity, hence youth, can be seen in the reduced strength of the alkali lines compared to main sequence stars.…”
Section: Surface Gravity and Chromospheric Activitymentioning
confidence: 99%